Can Urodynamic Parameters Predict Sling Revision for Voiding Dysfunction in Women Undergoing Synthetic Midurethral Sling Placement?. Issue 1 (January 2019) - Linder, Brian J.; Trabuco, Emanuel C.; Gebhart, John B.; Klingele, Christopher J.; Occhino, John A.; Elliott, Daniel S.; Lightner, Deborah J.
Abstract : Objective: The objective of the study was to evaluate the utility of urodynamic studies performed before primary midurethral sling placement for stress urinary incontinence in predicting the need for subsequent sling release for voiding dysfunction. Methods: The health records of women managed with primary synthetic midurethral sling placement at Mayo Clinic (Rochester, MN) from January 1, 2002, to December 31, 2012, were reviewed. The primary outcome was surgical sling release for postoperative voiding dysfunction (ie, prolonged retention, elevated postvoid residual volumes with new voiding symptoms, or de novo onset or worsening of overactive bladder symptoms). Logistic regression models were used to evaluate associations between potential clinical risk factors and the primary outcome. Results: Overall, 1629 women underwent primary synthetic midurethral sling placement during the study time frame, including 1081 patients (66%) who underwent a preoperative multichannel urodynamic evaluation. A sling release for voiding dysfunction was performed for 51 patients (3.1%) at a median of 1.9 months postoperatively (interquartile range, 1.3–9.3 months). Patients undergoing sling release were significantly more likely to have had retropubic sling placement ( P = 0.003) and concomitant prolapse surgery ( P = 0.005). On univariate analysis, no urodynamic parameters were associated with the risk of sling release; evaluated parameters included peak flow rate ( P = 0.20), postvoid residual volume ( P = 0.37), voiding without detrusor contraction ( P = 0.96), and detrusor pressure at maximal flow ( P = 0.23). Conclusions: Sling release for voiding dysfunction was rare in our cohort. No urodynamic parameters were associated with the risk of sling release. Abstract : In a study of more than 1000 women having both preoperative urodynamic studies and subsequently undergoing primary synthetic midurethral sling placement, no urodynamic parameters were associated with a risk of sling release for postoperative voiding dysfunction.